2023
DOI: 10.1155/2023/2696651
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Rebalancing Strategy for Shared e-Scooter Using Genetic Algorithm

Abstract: Shared e-scooters are provided as a free-floating service that can be freely rented and returned within the service area. Although this has a positive effect in terms of convenience for users of shared e-scooters, it is creating new urban problems, such as undermining the aesthetics of the city and obstructing the passage of pedestrians. Therefore, this study developed an optimal rebalancing algorithm to mitigate these problems and proposed an efficient operation plan. Complete relocation was performed to matc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Shui and Szeto [45] reviewed studies and found that they have focused on different characteristics of shared-bike rebalancing, such as objective functions (e.g., for distance, cost, and emissions), constraints (e.g., budget, service time, and inventory), optimization algorithms (exact or heuristic algorithms), deterministic or stochastic problems, and static or dynamic problems. Several other studies also summarized these challenges of rebalancing problems, including methodology [46], objectives [47,48], problem size [49], number of rebalancing vehicles [50,51], damaged bikes [52], equilibrium of station [53], and multi-step matching [54]. The present study focused on problems of rebalancing shared bikes under demand uncertainty and with predicted demand.…”
Section: A Rebalancing Of Sharing Servicesmentioning
confidence: 99%
See 1 more Smart Citation
“…Shui and Szeto [45] reviewed studies and found that they have focused on different characteristics of shared-bike rebalancing, such as objective functions (e.g., for distance, cost, and emissions), constraints (e.g., budget, service time, and inventory), optimization algorithms (exact or heuristic algorithms), deterministic or stochastic problems, and static or dynamic problems. Several other studies also summarized these challenges of rebalancing problems, including methodology [46], objectives [47,48], problem size [49], number of rebalancing vehicles [50,51], damaged bikes [52], equilibrium of station [53], and multi-step matching [54]. The present study focused on problems of rebalancing shared bikes under demand uncertainty and with predicted demand.…”
Section: A Rebalancing Of Sharing Servicesmentioning
confidence: 99%
“…Various heuristic algorithms have also been developed or applied to address these NP-hard optimization problems. These include (hybrid) genetic algorithm [48,71], ant colony optimization with CP (ACO-CP) [77], discrete-continuous hybrid model [38], CA [35], extended particle swarm optimization [52,53], greedygenetic heuristic [46], tabu search [49], neighborhood search [50], and neighborhood search-variable neighborhood descent [51]. Other algorithms can be found tabulated in the references [46][47][48]50].…”
Section: B Optimization Algorithmsmentioning
confidence: 99%